Prescribing Patterns in Hospital Inpatients - Nasim Karim; Sajid Abbas Jaffri; Zubair Ahmed Tirmizi (Journal of Bahria University Medical and Dental College)
Objective: To evaluate the prescribing patterns by an audit of prescriptions in hospital inpatients.